2022
DOI: 10.1093/asj/sjac210
|View full text |Cite
|
Sign up to set email alerts
|

PrabotulinumtoxinA vs OnabotulinumtoxinA for the Treatment of Adult Males With Moderate to Severe Glabellar Lines: Post-hoc Analyses of the Phase III Clinical Study Data

Abstract: Background Despite evidence of a growing interest among men in minimally invasive cosmetic procedures such as botulinum toxin injections, comparator clinical trial data in this population are limited. Objectives To compare the efficacy and safety of prabotulinumtoxinA and onabotulinumtoxinA for the treatment of males with moderate to severe glabellar lines. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is worth noting, however, that prabotulinumtoxin has been subjected to Phase 3 clinical trials that included diverse ethnic groups like Caucasians, African Americans, and Asians [15]. Moreover, in studies focused exclusively on men, prabotulinumtoxin has demonstrated comparable efficacy and side effect profiles to onabotulinumtoxin [16]. These considerations somewhat mitigate the limitations concerning gender and racial biases.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that prabotulinumtoxin has been subjected to Phase 3 clinical trials that included diverse ethnic groups like Caucasians, African Americans, and Asians [15]. Moreover, in studies focused exclusively on men, prabotulinumtoxin has demonstrated comparable efficacy and side effect profiles to onabotulinumtoxin [16]. These considerations somewhat mitigate the limitations concerning gender and racial biases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar in methodology to previously reported subgroup analyses of prabotulinumtoxinA-treated patients, [14][15][16] data extracted from these single-dose glabellar line studies were pooled and summarized-in this case, for patients less than 65 years of age and those 65 years of age and older. Safety data are reported for all 737 prabotulinumtoxinA-treated participants.…”
Section: Statistical Methods Of the Post Hoc Analysesmentioning
confidence: 99%
“…Kaplan-Meier methodology was used to calculate the durability of response (number of days at which 50% of patients had stopped responding) for the two age groups. As in each of the previous subgroup analyses, [14][15][16] the key efficacy endpoint was the percentage of responders with a ≥1-point improvement from baseline based on the GLS at maximum frown by investigator assessment. The other efficacy endpoint based on the GLS was the percentage of responders with a post-baseline score of 0 or 1 (none or mild) at maximum frown.…”
Section: Statistical Methods Of the Post Hoc Analysesmentioning
confidence: 99%
See 1 more Smart Citation